Modelling and simulation for autonomous systems : third International Workshop, MESAS 2016, Rome, Italy, June 15-16, 2016, Revised selected papers /: third International Workshop, MESAS 2016, Rome, Italy, June 15-16, 2016, Revised selected papers. (2016) - Unknown
No abstract available